Pyrazoles as potential anti-angiogenesis agents: a contemporary overview - Kasiotis, Konstantinos M.; Tzanetou, Evangelia N.; Haroutounian, Serkos A. (Frontiers in Chemistry, 2014)
Angiogenesis is a mulit-step process by which new blood vessels are formed from preexisting vasculature. It is a key rate limiting factor in tumor growth since new blood vessels are necessary to increase tumor size. In this context it has been shown that anti-angiogenic factors can be used in cancer therapy. Among the plethora of heterocyclic compounds administered as anti-angiogenesis agents, pyrazoles constitute one of the bottlenecks of this category. Currently several pyrazole based compounds are administered or are in Phase II and III trials and new targets emerge. It is highly possible that the advent of the next two decades will lead to the discovery and use of additional pyrazoles whose anti-angiogenic profile will position them in the forefront of the battle of various malignancies. The present review is an attempt to focus on those pyrazoles that arise as anti-angiogenesis agents commenting both on the chemistry and bioactivity that these exhibit aiming to contribute to the perspectives that they hold for future research.